2019
DOI: 10.1038/s41380-019-0426-0
|View full text |Cite
|
Sign up to set email alerts
|

Excitation-inhibition balance as a framework for investigating mechanisms in neuropsychiatric disorders

Abstract: In 2003 Rubenstein and Merzenich hypothesized that some forms of Autism (ASD) might be caused by a reduction in signal-to-noise in key neural circuits, which could be the result of changes in excitatory-inhibitory (E-I) balance. Here, we have clarified the concept of E-I balance, and updated the original hypothesis in light of the field's increasingly sophisticated understanding of neuronal circuits. We discuss how specific developmental mechanisms, which reduce inhibition, affect cortical and hippocampal func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

28
540
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 655 publications
(619 citation statements)
references
References 80 publications
(93 reference statements)
28
540
3
3
Order By: Relevance
“…In this regard, both the MS and PNFLx models have critical periods spanning from P2-14 and P2-11 respectively 74,76,77 . These temporal windows overlap with distinct critical periods including the stress hyporesponsive period 107-109 , a neurodevelopmental window for the refinement of multiple cortical circuits 1,2 , including the maturation of serotonergic afferents to the cortex 110,111 , and the tuning of excitation-inhibition balance across cortical microcircuits 34,112,113 . A recent report indicates that hM3Dq DREADD activation of the medial prefrontal cortex during postnatal life can abrogate the influence of maternal separation on oligodendrogenesis and despair-like behavior 83 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, both the MS and PNFLx models have critical periods spanning from P2-14 and P2-11 respectively 74,76,77 . These temporal windows overlap with distinct critical periods including the stress hyporesponsive period 107-109 , a neurodevelopmental window for the refinement of multiple cortical circuits 1,2 , including the maturation of serotonergic afferents to the cortex 110,111 , and the tuning of excitation-inhibition balance across cortical microcircuits 34,112,113 . A recent report indicates that hM3Dq DREADD activation of the medial prefrontal cortex during postnatal life can abrogate the influence of maternal separation on oligodendrogenesis and despair-like behavior 83 .…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, a commonality noted across these animal models is the fact that multiple molecular, cellular, functional and behavioral changes often persist throughout the animal's lifespan 5,11,25 . Amongst the underlying mechanisms implicated in the establishment of such long-lasting changes in response to early life perturbations are a dysregulation of the hormonal stress response pathway 22,26-30 , serotonergic system 31-33 , and emergence of excitation-inhibition balance within key cortical neurocircuits 34,35 .…”
Section: Introductionmentioning
confidence: 99%
“…However, coming to a better understanding of how E:I balance is affected across a heterogeneous mixture of autistic individuals has proven to be challenging because of the limited availability of robust E:I biomarkers that are non-invasive and applicable in humans and which can be measured on a large scale. A majority of the literature about E:I balance in autism extends from investigations of prominent single gene mutations associated with autism and the animal model research around these genes 2,3 . This leaves a significant gap in evaluating the E:I theory on a larger majority of the autistic population.…”
mentioning
confidence: 99%
“…A variety of in vivo studies have demonstrated that non-competitive NMDAr antagonism increases the firing rate of PFC pyramidal neurons reducing their synchrony, and enhancing broadband gamma activity 33,[46][47][48][49] . This broadband gamma enhancement is thought of as an aberrant and diffuse noise at the network level that can cause dysfunction in cognitive and sensory-motor integration 17,50 . In our study, gamma increase after KET injection was robust in the PFC, with subtle effects in the HPC (see also Figure S1A).…”
Section: Discussionmentioning
confidence: 99%